A critical appraisal of complications of percutaneous nephrolithotomy in paediatric patients using adult instruments. (14th February 2014) - Goyal, Neeraj Kumar; Goel, Apul; Sankhwar, Satya Narayan; Singh, Vishwajeet; Singh, Bhupendra Pal; Sinha, Rahul Janak; Dalela, Divakar; Yadav, Rahul
Abstract : Objective: To evaluate the complications (using the CROES Clavien scoring system) and various factors affecting them in children undergoing percutaneous nephrolithotomy (PCNL). Patients and Methods: We analysed prospectively maintained data of paediatric PCNL (patients ≤17 years) from January 2008 to December 2012. Stone complexity was defined according to validated Guy's stone score (GSS). Procedures were performed in the prone position by experienced urologists. The tract was dilated (24–30F) under fluoroscopic guidance, and an adult rigid nephroscope complemented with a cystoscope/ureteroscope were used. Complications were recorded according to the CROES‐Clavien score, recently defined by the Clinical Research Office of the Endourological Society (CROES) Study Group. Results: The study group comprised 158 procedures performed in 153 children (98 boys and 55 girls), with a mean (range) age 10.03 ± 4.51 (2–17) years. The mean (range) stone burden was 376.68 ± 265.23 (150–2400) mm 2 . The distribution of cases according to the GSS was 31% grade I, 35.4% grade II, 19% grade III, and 14.6% grade IV. The stone‐free rate of PCNL monotherapy was 85.4%, which increased to 93.7% after relook PCNL/extracorporeal shock wave lithotripsy. In all, 62 children (39.2%) had operative complications; 84% were minor, i.e. Clavien grade 1/2, and managed conservatively. Stone size, GSS, tract size, number of punctures and operation duration were significantly associated with complications on univariate analysis ( P < 0.05). However, on multivariate logistic regression analysis, operation duration was the only independent risk factor associated with complications (95% confidence interval: 1.013–1.065, odds ratio = 1.04; P = 0.038). Conclusions: Percutaneous nephrolithotomy in children using adult instruments is an effective and safe procedure for managing simple as well as complex renal calculi. Assignment of specific Clavien scores to all possible PCNL complications by the CROES PCNL Study Group have improved precision in reporting complications in a standard objective format, including the minor ones. Such models are very useful for making inter‐observer comparisons to obtain clinically relevant inferences. Mean operation duration is the only independent factor affecting complications of the procedure.